Implementing a participatory model of place-based stewardship for inclusive wetland management: A community case study - Reeves, Jessica M.; Bonney, Patrick R. (Frontiers in Water, 2023)
The inclusion of local values and an appreciation for different ways of knowing are increasingly considered core principles in wetland management but can be difficult to achieve in practice. This Community Case Study describes the development and impacts of a participatory action research (PAR) project focused on the creation of a community-led stewardship and knowledge sharing in a rural coastal community in Victoria, Australia. The project, Living Bung Yarnda, was designed around four dimensions - vision, knowledge, narrative, and capacity - that align with key principles of PAR and guided the process of knowledge building and exchange. Working with a range of stakeholders, including environmentally-focussed community members, government agencies and Traditional Owners groups, we aimed to discover pathways for the inclusion of local knowledge, lived experience, and acts of care by community members in governance processes. The case description illustrates how embedded knowledge in this community is currently undervalued by management agencies but, if harnessed, can contribute to more holistic and equitable forms of wetland management. We conclude with reflections on the development of the project, emphasising the role of academic researchers in fostering relationships between community and management authorities that is built on trust, humility and a willingness to find a common language.